2016
DOI: 10.1038/srep36162
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose prevents aggregation of exosomes and cryodamage

Abstract: Exosomes are important mediators in intercellular communication. Released by many cell types, they transport proteins, lipids, and nucleic acids to distant recipient cells and contribute to important physiopathological processes. Standard current exosome isolation methods based on differential centrifugation protocols tend to induce aggregation of particles in highly concentrated suspensions and freezing of exosomes can induce damage and inconsistent biological activity. Trehalose is a natural, non-toxic sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
206
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(225 citation statements)
references
References 50 publications
5
206
1
Order By: Relevance
“…Our experiment also revealed that vitrification in the absence of trehalose (0.0 M) impairs developmental competence in vitri- (Bosch et al, 2016) and stabilizing the structural and functional integrity of cell membrane in lowwater media (Kaushik & Bhat, 2003;Olsson, Jansson, & Swenson, 2016…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our experiment also revealed that vitrification in the absence of trehalose (0.0 M) impairs developmental competence in vitri- (Bosch et al, 2016) and stabilizing the structural and functional integrity of cell membrane in lowwater media (Kaushik & Bhat, 2003;Olsson, Jansson, & Swenson, 2016…”
Section: Discussionsupporting
confidence: 56%
“…Our findings suggest that the detrimental effects of CPAs on ZP were remarkably reduced in the presence of trehalose. Trehalose has been recently found to be useful in preventing the cryodamage (Bosch et al, ) and stabilizing the structural and functional integrity of cell membrane in low‐water media (Kaushik & Bhat, ; Olsson, Jansson, & Swenson, ) . The results of several studies show that stabilizing effects of sugars in general and trehalose in particular, are related to a specific interaction of sugars with biological molecules in bilayer membranes (Jain & Roy, ; Konov et al, ; Olsson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that a fraction (;50%) of IL-32 was secreted as a free, nonvesicular protein. Whether this is due to disruption of vesicles and release of IL-32 47 or whether IL-32 is also released from the cells as a free protein remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are commonly considered to be a homogeneously shaped group of vesicles, sized 40-100 nm in diameter (20). On the other hand, an abundance of morphological diversity has emerged when extracellular vesicles from bodily fluids (11-13, 15, 16) and cell culture supernatant (29)(30)(31) were studied using cryo-electron microscopy (cryo-EM), a method which allows visualization of membrane bilayers and internal features (11)(12)(13)31). However, thorough morphological studies using cryo-EM on exosomes purified from a single cell type are lacking to date.…”
Section: Introductionmentioning
confidence: 99%